Simulation of muscle-tendon complex during human movements - Fukashiro, S.; Hay, D. C.; Yoshioka, S.; Nagano, A. (International Journal of Sport & Health Science, 2005)
The purpose of this paper was to review the research findings regarding the biomechanical behavior of the muscle-tendon complex (MTC) during dynamic human movements, especially those obtained using computer simulation. Specific studies conducted by the authors using the free vibration technique and MTC modeling have been discussed in detail. For determining individual viscoelastic characteristics of the human triceps surae MTC groups, a race difference between Black and White college athletes was investigated using the free vibration technique. It was found that the muscle stiffness was greater among Black athletes. Through computer simulation using a Hill-type MTC model, the benefit of making a countermovement was investigated in relation to the length ratio between the contractile element (CE) and the series elastic element (SEE) and the compliance of the MTC. The integral roles of the SEE were simulated in a cyclic human heel-raise exercise. It was revealed that it is beneficial to make a countermovement for explosive activities like vertical jumping, and the benefit of making a countermovement increases as the compliance of the MTC increases. Also, using a MTC model, the effects of moment arm length on kinetic outputs of the musculoskeletal system were evaluated. It was found that longer moment arm resulted in smaller joint moment development, smaller joint power output and smaller joint work output in the larger plantarflexion angular velocity region. It can be said that computer simulation is a powerful tool for determining and evaluating MTC behavior during dynamic human movements.